The CacyBP/SIP Protein is Sumoylated in Neuroblastoma NB2a Cells - Wasik, Urszula (Springer US, 2013)
The Calcyclin binding protein and Siah-1 interacting protein (CacyBP/SIP) protein is highly expressed in mammalian brain as well as in neuroblastoma NB2a cells and pheochromocytoma PC12 cells. This protein interacts with several targets such as cytoskeletal proteins or ERK1/2 kinase and seems to be involved in many cellular processes. In this work we examined a post-translational modification of CacyBP/SIP which might have an effect on its function. Since theoretical analysis of the amino acid sequence of CacyBP/SIP indicated several lysine residues which could potentially be sumoylated we checked experimentally whether this protein might be modified by SUMO attachment. We have shown that indeed CacyBP/SIP bound the E2 SUMO ligase, Ubc9, in neuroblastoma NB2a cell extract and was sumoylated in these cells. By fractionation of NB2a cell extract we have found that, contrary to the majority of SUMO-modified proteins, sumoylated CacyBP/SIP is present in the cytoplasmic and not in the nuclear fraction. We have also established that lysine 16 is the residue which undergoes sumoylation in the CacyBP/SIP protein.